2013
DOI: 10.4136/ambi-agua.1155
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals in the waste and in the water discharge area of municipal solid waste

Abstract: The county of Paranaguá discards 80 tons of municipal solid waste (MSW) daily in the Embocuí landfill without proper treatment. The present study aimed to evaluate the concentration of arsenic (As), cadmium (Cd), chromium (Cr), lead (Pb) and mercury (Hg) in the dump area and to compare it with reference values for soil and water quality stipulated by CETESB (2005). The methodology of the study involved the collection of waste samples (organic waste mixed with soil) from a depth of 1 m deep at 12 points of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…They observed that there is a tendency to decrease the Zn, Cu, Pb and Cr levels in the lower layers of the soil, even though they have concentrations above the reference values in the superficial layer. This reduction of metals can occur due to factors such as the retention of metal ions in the mass of garbage mixed with the soil, the adsorption of the metals in the soil particles and the precipitation of the metals in the stable forms (Cavallet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…They observed that there is a tendency to decrease the Zn, Cu, Pb and Cr levels in the lower layers of the soil, even though they have concentrations above the reference values in the superficial layer. This reduction of metals can occur due to factors such as the retention of metal ions in the mass of garbage mixed with the soil, the adsorption of the metals in the soil particles and the precipitation of the metals in the stable forms (Cavallet et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Manganese is essential, however, in excess it is associated with neurological diseases and behavioral disorders. High levels of copper cause gastrointestinal symptoms, such as diarrhea, abdominal pain and nausea (Cavallet, et al, 2013). A study conducted by Li et al (2013) aimed to quantify traces of metals and to map the spatial distribution of health risk caused by these elements in the Henan-Liaocheng Irrigation Area (HLIA) in China.…”
Section: Introductionmentioning
confidence: 99%
“…Nos aterros controlados e nos lixões não há impermeabilização e as substâncias provenientes da decomposição dos resíduos infiltram no solo atingindo águas subterrâneas e são carreadas pelas chuvas contaminando o meio ambiente. Outro agravante é que esses contaminantes irão persistir no ambiente até décadas após o fechamento do aterro (Cavallet et al, 2013;Santana et al, 2007).…”
Section: Introductionunclassified